Analysis of Islamic Bank Performance Through Evaluation Maqasid Syariah Index (Comparative Study of Bank Muamalat and Bank Syariah Indonesia for the 2021-2025 Period) - Suraya; Abdullah Ahadish Shamad Muis (LP2M IAIN Palopo, 2026)
This study aim for analyze and compare performance of Bank Muamalat Indonesia and Bank Syariah Indonesia using Maqasid Syariah Index (MSI) approach during 2021–2025 period. Research This based on measurement performance Islamic banking in Indonesia which is still dominated by indicators finance conventional so that not yet fully reflect Sharia objectives and values. The study used a quantitative approach with descriptive-comparative and inferential methods. The data used were secondary data obtained from the annual financial statements and annual reports of Bank Muamalat Indonesia and Bank Syariah Indonesia for the 2021–2025 period. The Maqasid Syariah Index was calculated using the Simple Additive Weighting (SAW) method based on three dimensions of Abu Zahrah's maqasid syariah, namely tahdzib al-fard (educating individuals), iqamah al-'adl (upholding justice), and jalb al-maslahah (realizing benefits). Data analysis techniques included trend analysis, descriptive statistics, normality tests using the Shapiro-Wilk test, and difference tests using the Independent Sample t-test. The results showed that the performance of Bank Syariah Indonesia tended to be more stable despite fluctuations during the study period, while Bank Muamalat Indonesia showed higher fluctuations in the MSI value. The results of the difference test indicate that there is no significant difference between the performance of the Maqasid Syariah Index of Bank Muamalat Indonesia and Bank Syariah Indonesia with a significance value of. 771 (p >.05). This finding indicates that differences in asset scale, service network, and institutional characteristics do not directly determine the success of achieving the maqasid syariah. This study provides implications that the Maqasid Syariah Index can be used as an alternative measurement of Islamic bank performance that is more comprehensive than conventional financial indicators because it is able to assess aspects of justice, welfare, and social function of Islamic banking.